Effects of Spray Nozzle and Fungicide Mode of Action on Control of Microdochium Patch on an Annual Bluegrass Putting Green in Western Oregon. Issue 1 (15th September 2016) - McDonald, B.W.; Mattox, C.M.; Kowalewski, A.R.; Mosdell, D.K.
Abstract : Core Ideas: Nozzle‐type spray volume and topical activity on Microdochium patch were evaluated. At equal spray volumes, TeeJet XR nozzles cover more spray area than 1/4TTJ nozzles. Smaller droplets and higher coverage maximize Microdochium patch control.